Removal of selected contaminants of the soil and water environment on a model isolation barrier - Jolanta Sobik-Szołtysek (Desalination and Water Treatment)
Landfill leachate poses a threat to the soil and water environment. Protection against their migration is provided by sealing the bottom and sides of the landfill called containment barriers. Natural clay are used for their construction. Fine-grained industrial waste of a mineral nature has been proposed as an alternative to them. Two-component mixtures of ash from solid fuel combustion and waste coal sludge have been developed. The basic expected property of an isolation barrier is its impermeability. Also important is the sorption capacity of the material from which the barrier is made. Hence, the purpose of the study was to evaluate the potential of the obtained mixtures to remove selected heavy metals and PAHs from aqueous solutions. The examinations of static batch sorption and sorption under flow conditions were conducted in columns. Solutions containing Zn(II), Cd(II), and Pb(II) ions with initial concentrations of 100, 200, and 500 mg L−1 were used in the experiment. For all mixtures, regardless of the initial concentration, batch sorption of metals exceeded 99%. In polymetallic solutions, the competitive phenomena between zinc and cadmium ions were confirmed, resulting in a decrease in the efficiency of their removal from the solution. The column tests carried out using raw leachate from a municipal landfill showed the effectiveness of the mixture in removing PAHs, particularly noticeable for di- and hexacyclic hydrocarbons. The removal rate of the 5 analyzed PAH groups ranged from 47.49 to 70.0%. The obtained results confirmed the high sorption capacity of the tested material, which allows considering its use as a sorbent in environmental engineering.